Experimental Investigation of the Influence for Stoping Sequence and Granular Grading on Lateral Pressure during the Nonpillar Sublevel Caving Mining - Yang Liu; Rongxing He; Fengyu Ren; Jianli Cao; Dongjie Zhang; Yanjun Zhou; Huan Liu; Guanghui Li; Jing Zhang (Advances in Civil Engineering)
In this study, a self-designed scaled physical model was conducted to investigate the variation laws of lateral pressure under different stoping sequences and granular gradings, and drawing ore in the experiments was used to simulate the mining process. Under the limiting equilibrium state, the values of lateral pressure increased exponentially with the increasing depth of granular media, and the growth rate of lateral pressure gradually decreased as the depth of granular media increased. Then, the laboratory results indicated that the distribution laws of lateral pressure were divided into three parts, namely, the drawing influencing region, the upper descending zone, and the central growth area. As the height of the isolated extraction zone (IEZ) increased, the scope of the drawing influencing region and the upper descending zone increased, while the range of central growth area decreased. In the case of an invariable height of IEZ, more reduction ratio and the scope for drawing influencing region could be appeared in the lower wall. Increasing the space between the drawpoints and granular grading were an effective way to control the reduction rate of lateral pressure in the drawing influencing region, while the scope of the above parts kept stable. Moreover, the average values of lateral pressure showed an increasing trend as the granular grading decreased at the same number of drawing ore.